Genome-Wide Identification of the PMEI Gene Family in Tea Plant and Functional Analysis of CsPMEI2 and CsPMEI4 Through Ectopic Overexpression - Li, Bo; Wang, Huan; He, Shan; Ding, Zhaotang; Wang, Yu; Li, Nana; Hao, Xinyuan; Wang, Lu; Yang, Yajun; Qian, Wenjun (Frontiers in Plant Science, 2022)
Pectin methylesterase inhibitor (PMEI) inhibits pectin methylesterase (PME) activity at post-translation level, which plays core roles in vegetative and reproductive processes and various stress responses of plants. However, the roles of PMEIs in tea plant are still undiscovered. Herein, a total of 51 CsPMEIs genes were identified from tea plant genome. CsPMEI1-4 transcripts were varied in different tea plant tissues and regulated by various treatments, including biotic and abiotic stresses, sugar treatments, cold acclimation and bud dormancy. Overexpression of CsPMEI4 slightly decreased cold tolerance of transgenic Arabidopsis associated with lower electrolyte leakage, soluble sugars contents and transcripts of many cold-induced genes as compared to wild type plants. Under long-day and short-day conditions, CsPMEI2/4 promoted early flowering phenotypes in transgenic Arabidopsis along with higher expression levels of many flowering-related genes. Moreover, overexpression of CsPMEI2/4 decreased PME activity, but increased sugars contents (sucrose, glucose and fructose) in transgenic Arabidopsis as compared with wild type plants under short-day condition. These results indicate that CsPMEIs are widely involved in tea plant vegetative and reproductive processes, and also in various stress responses. Moreover, CsPMEI4 negatively regulated cold response, meanwhile, CsPMEI2/4 promoted early flowering of transgenic Arabidopsis via the autonomous pathway. Collectively, these results open new perspectives on the roles of PMEIs in tea plant.